Dynamics of Peyrard Bishop model of DNA under the influence of solvent interaction. (2022) - Joy, Christy Maria; Ayyappam, N.; Kavitha, L.
Abstract: In this paper we study the effect of solvent potential interaction on the dynamics of Peyrard Bishop model of DNA. The potential energy in the Hamiltonian arises from the morse potential beacause of hydrogen bonding and solvent potential due to environmental interaction. We invoke the semi discrete approximation and the dynamics is found to be governed by the Nonlinear Schrodinger equation(NLS). The propagation of envelope soliton in DNA is analyzed for various contributing factors.